Coronary artery disease risk factors affected by RNA modification-related genetic variants - Li, Ru; Zhang, Huan; Tang, Fan; Duan, Chengcheng; Liu, Dan; Wu, Naqiong; Zhang, Yonghong; Wang, Laiyuan; Mo, Xingbo (Frontiers in Cardiovascular Medicine, 2022)
Background: Single nucleotide polymorphisms that affect RNA modification (RNAm-SNPs) may have functional roles in coronary artery disease (CAD). The aim of this study was to identify RNAm-SNPs in CAD susceptibility loci and highlight potential risk factors. Methods: CAD-associated RNAm-SNPs were identified in the CARDIoGRAMplusC4D and UK Biobank genome-wide association studies. Gene expression and circulating protein levels affected by the RNAm-SNPs were identified by QTL analyses. Cell experiments and Mendelian randomization (MR) methods were applied to test whether the gene expression levels were associated with CAD. Results: We identified 81 RNAm-SNPs that were associated with CAD or acute myocardial infarction (AMI), including m6A-, m1A-, m5C-, A-to-I- and m7G-related SNPs. The m6A-SNPs rs3739998 in JCAD, rs148172130 in RPL14 and rs12190287 in TCF21 and the m7G-SNP rs186643756 in PVT1 were genome-wide significant. The RNAm-SNPs were associated with gene expression (e.g., MRAS, DHX36, TCF21, JCAD and SH2B3), and the expression levels were associated with CAD. Differential m6A methylation and differential expression in FTO-overexpressing human aorta smooth muscle cells and peripheral blood mononuclear cells of CAD patients and controls were detected. The RNAm-SNPs were associated with circulating levels of proteins with specific biological functions, such as blood coagulation, and the proteins (e.g., cardiotrophin-1) were confirmed to be associated with CAD and AMI in MR analyses. Conclusion: The present study identified RNAm-SNPs in CAD susceptibility genes, gene expression and circulating proteins as risk factors for CAD and suggested that RNA modification may play a role in the pathogenesis of CAD.